Deconstructing the shopping experience of tourists to the Dubai Shopping Festival - Sangeeta Peter (Taylor & Francis Group, 2016)
Shopping Festivals are being promoted as tourism products, thus attracting large number of tourists. Recent years have seen the growth of shopping festivals and shopping gaining greater significance in tourism, given its contribution to the retail and tourism sectors of a destination. This empirical study discusses the shopping experience of international tourists visiting the Dubai Shopping Festival (DSF). Data was collected from 603 international, English speaking tourists, using the mall intercept technique, during the XVIII edition of the DSF from January to February 2013. Exploratory factor analysis was employed to delineate seven factors which suggest that tourists do not shop independent of the shopping environment. Shopping experience involves much more than the acquisition of goods. Store Attribute, Mall Atmospherics, Safety, Mall Amenities, Product Attribute and Staff Service positively influence tourists’ shopping experience. The findings of this study will help the stakeholders in designing specific products and shopping environments.